Effect of the naturally occurring salt 'Kanwa' as a fertilizer on the productivity of Stylosanthes in the subhumid zone of Nigeria - Mohamed-Saleem, M.A.; Otsyina, R.M. (Springer, 1987)
Reports the response of two stylo cultivars, viz, stylosanthes hamata cv verano and stylosanthes guianensis cv cook to 'Kanwa' - a naturally occuring salt traditionally used as a cattle lick - but which shows the presence of various essential nutrients for plants. Discusses the implications to agropastoral production systems